Growth history of hepatitis C virus among HIV/HCV co-infected patients in Guizhou Province - Yang, Xiu-Cheng; Hong, Zhang-Ping; Wang, Yi; Meng, Nan; Hu, Yong; Xiong, Qian-Yu; Qin, Da-Wen; Shen, Du; Yang, Xing-Lin (Frontiers in Genetics, 2023)
The evolutionary and epidemiological history and the regional differences of various Hepatitis C virus genotypes are complex. Our aim was to better understand the molecular epidemiology and evolutionary dynamics of HCV among HIV/HCV co-infected individuals in Guizhou province. This information could contribute to improve HCV prevention and control strategies in Guizhou and surrounding provinces. The HCV RNA was extracted from serum of HIV/HCV co-infected patients, and reverse transcription/nested PCR was performed to amplify nucleotide sequences of the C-E1 region. Then, the successfully amplified sequences were selected for phylogenetic analysis. The available C-E1 region reference sequences from the surrounding provinces of Guizhou were retrieved in GenBank, and the evolutionary analysis by Bayesian Markov Chain Monte Carlo algorithm was performed using BEAST software to reconstruct a phylogeographic tree to explore their migration patterns. Finally, the epidemiological history of HCV in Guizhou region was retraced by reconstructing Bayesian skyline plots after excluding sequences from surrounding provinces. Among 186 HIV/HCV co-infected patients, the C-E1 region sequence was successfully amplified in 177 cases. Phylogenetic analysis classified these sequences into six subtypes: 1a, 1b, 3a, 3b, 6a, and 6n. Among them, subtype 6a was the most dominant strain (n=70), followed by 3b (n=55), 1b (n=31), 3a (n=11), 1a (n=8), and 6n (n=2). By reconstructing the phylogeographic tree, we estimated that strain 6a in Guizhou mainly originated from Yunnan and Guangxi, while strain 3b emerged due to transmission from the IDU network in Yunnan. Subtypes 1b, 3a, 3b, and 6a, as the major subtypes of HCV in HIV/HCV co-infected individuals in Guizhou, emerged and later grew rapidly than the national average. Notably, BSPs of the currently prevalent HCV predominant strain subtype 6a in Guizhou showed a rapid population growth since 2004. Although the growth rate slowed down around 2010, this growth has continued to date. Overall, despite the improvement and implementation of a series of HCV prevention and control policies and measures, a delayed growth pattern may indicate a unique history of the spread of 6a in Guizhou. Its trend as the dominant strain in Guizhou in recent years may continue to increase slowly over subsequent years.